2018
DOI: 10.1186/s12885-018-4616-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative controlling nutritional status (CONUT) score as a predictor of long-term outcome after curative resection followed by adjuvant chemotherapy in stage II-III gastric Cancer

Abstract: BackgroundThe prognostic value of preoperative controlling nutritional status (CONUT) has been reported in many malignancies. In present study, we aimed to clarify the prognostic impact of CONUT in gastric cancer (GC) receiving curative resection and adjuvant chemotherapy.MethodsWe retrospectively reviewed 697 consecutive patients undergoing curative surgery followed by adjuvant chemotherapy for Stage II-III GC between November 2000 and September 2012. Patients were classified into high (≥3) and low (≤2) CONUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 30 publications
2
72
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to uncover that preoperative CONUT-CTC score is associated with tumour progression and can be considered an independent marker for better predicting the prognosis of patients with CRC treated with curative resection. The CONUT score is proposed as a blood-based marker for reflecting host immune-nutritional status [20,23], and growing evidence has shown that higher preoperative CONUT score indicates worse nutritional condition and pro-tumour immunity status [20,[22][23][24], which facilitates the migration, invasion and metastasis of tumour cells [31][32][33][34][35] and affects patients' prognosis with multiple solid tumours [21], including lung [36], liver [37], gastric [38] and colorectal cancer [22][23][24]. As a component of peripheral blood in patients with cancer, CTC was originally considered to be an important mediator of tumour recurrence and metastasis [6] and was also reported to be significantly associated with poor prognosis in a variety of malignancies [9,11,39].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to uncover that preoperative CONUT-CTC score is associated with tumour progression and can be considered an independent marker for better predicting the prognosis of patients with CRC treated with curative resection. The CONUT score is proposed as a blood-based marker for reflecting host immune-nutritional status [20,23], and growing evidence has shown that higher preoperative CONUT score indicates worse nutritional condition and pro-tumour immunity status [20,[22][23][24], which facilitates the migration, invasion and metastasis of tumour cells [31][32][33][34][35] and affects patients' prognosis with multiple solid tumours [21], including lung [36], liver [37], gastric [38] and colorectal cancer [22][23][24]. As a component of peripheral blood in patients with cancer, CTC was originally considered to be an important mediator of tumour recurrence and metastasis [6] and was also reported to be significantly associated with poor prognosis in a variety of malignancies [9,11,39].…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential role of systematic inflammation and nutrition status in tumor progression and their associations with oncological outcomes, several biomarkers that reflect the above two status have been explored in UTUC including neutrophil to lymphocyte ratio, albumin to globulin ratio, nutritional index, and controlling nutritional status (CONUT) score . Of them, CONUT score, a novel biomarker which is calculated from serum albumin, total lymphocyte counts, and total cholesterol concentrations, has shown its independent prognostic significance in various solid tumor types such as hepatocellular carcinoma, gastric cancer, and colorectal cancer . It reflects individuals’ nutrition status, immunological function, protein and lipids metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, it was 3 according to the ROC curve, which was in accordance with previous studies. [19][20][21] PSM analysis has been used in many studies to balance subgroups across selected factors. 22 In our study, to balance the baseline characteristics of preoperative covariates between the two groups, we used the PSM method.…”
Section: Discussionmentioning
confidence: 99%